Adsorption of Phenol from Aqueous Solution by Aminated Hypercrosslinked Polymers - Yue Sun; Jin-Long Chen; Ai-Min Li; Fu-Qiang Liu; Quan-Xing Zhang (Adsorption Science & Technology)
The adsorption of phenol from aqueous solution onto the hypercrosslinked polymeric adsorbent NDA-100 and its dimethylamine aminated derivatives AH-1, AH-2 and AH-3, the commercial resin Amberlite XAD-4 and the weakly basic anion-exchange resin D301 was compared. Of the tested polymers, the aminated hypercrosslinked resins had the highest adsorption capacities. The empirical Freundlich equation was successfully employed to describe the adsorption process. The specific surface area and the micropore structure of the adsorbent together with the tertiary amino group on the matrix affected the adsorption performance towards phenol. Furthermore, these factors also influenced the thermodynamic properties. Kinetic studies demonstrated that the presence of the tertiary amino group on the polymer matrix decreased the adsorption rate and increased the apparent activation energy of the adsorption process.